Endemicity change of hepatitis A infection necessitates vaccination in food handlers: An Indian perspective - Bhaskar Shenoy; Anar Andani; Shafi Kolhapure; Ashish Agrawal; Jaydeep Mazumdar (Taylor & Francis Group, 2022)
In the last two decades, outbreaks due to the foodborne hepatitis A virus (HAV) have been frequently reported in India, with adolescents and adults primarily affected. In India, most food handlers are adolescents and young adults who might be exposed to unsatisfactory environmental conditions and poor water quality. This increases the risk of HAV infection and consequently compounds the risk of HAV transmission from food handlers to susceptible populations. Given the shift in hepatitis A endemicity from high to intermediate levels in India, implementing the vaccination of food handlers has become important as it can also contribute to the elimination of hepatitis A in India. This narrative review makes a case for hepatitis A immunization of food handlers in India considering the growing food industry, evolving food culture, and the substantial burden caused by hepatitis A outbreaks.